TINDAKAN KOMUNIKATIF KOMUNITAS VIRTUAL UNTUK MENGURANGI DISINFORMASI PEMBERITAAN POLITIK DI MEDIA SOSIAL - Azwar Azwar (Universitas Padjadjaran, 2022)
AbstractThis paper is part of the research results that reveal the communicative action by the virtual community Forum Anti Fitnah Hasut dan Hoax (FAFHH) on Facebook to reduce disinformation on social media as a new public sphere. This paper is viewed from the perspective of the Theory of Communicative Action initiated by Jurgen Habermas. Habermas's idea is very important for this paper because it offers a broader framework for understanding social media as a public sphere. It is also to understand how individuals or communities seek to achieve common understanding within groups to promote cooperation, not just to achieve personal goals. This paper uses a critical, qualitative paradigm with a virtual ethnographic method. Data collection was carried out by observing participants in virtual communities FAFHH on Facebook. In addition to observations, the author also conducted in-depth interviews with virtual community managers (admins and moderators). The results of this study indicate that the FAFHH virtual community has fulfilled the requirements as a public sphere. In addition, the FAFHH virtual community has also fulfilled the validity claim in communicative actions.Keywords: disinformation, virtual community, social media, communicative action, public sphere.